2020
DOI: 10.3390/en13123108
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Differences in Carbon Intensity in Polish Households

Abstract: Knowledge about the driving forces behind greenhouse gasses (GHG) emissions is crucial for informed and evidence-based policy towards mitigation of GHG emission and changing production and consumption patterns. Both national and regional-level authorities are capable of addressing their actions more effectively if they have information about the spatial distribution of phenomena related to the policies they conduct. In this context, the main aim of this paper is to explain the regional differences in carbon in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Behavior is the general term for a series of purposeful activities of people [18,19]. Low-carbon and proenvironmental behaviors specifically refer to the behavior of ensuring the sustainability of the ecosystem while maintaining normal economic development [20].…”
Section: Residents' Low-carbon Behaviormentioning
confidence: 99%
“…Behavior is the general term for a series of purposeful activities of people [18,19]. Low-carbon and proenvironmental behaviors specifically refer to the behavior of ensuring the sustainability of the ecosystem while maintaining normal economic development [20].…”
Section: Residents' Low-carbon Behaviormentioning
confidence: 99%
“…This improvement is indicated in the context of resource use by transport [5]. There is also a strong link between economic development and the continual increase in energy consumption on a global scale [6][7][8]. A similar relationship was noticed in transport, and therefore, attention has been paid to the need to promote one of the paradigms of sustainable development, i.e., decoupling [9,10].…”
Section: Introduction 1presentation Of Research Problemsmentioning
confidence: 93%
“…Since the 1970s, an increasing number of scholars have been involved in research on land-use carbon emissions, summarized into the following areas and features: research related to land-use carbon sources and sinks from the perspective of the carbon cycle in terrestrial ecosystems, mainly dealing with the accounting of land-use carbon stocks and fluxes and their influencing factors [7,8]; correlation analysis of the relationship between carbon emissions and economic growth or factors of production based on land carbon emissions using econometric methods such as the gray correlation model [9], the coupled coordination degree model [10], and the decoupling model [11]; and research related to low-carbon development policies for land use under the "dual carbon" goal, that is, to portray the evolution models of land-use carbon emissions through methods such as spatial autocorrelation and cold-hot spot analysis and to further propose their policy implications. For example, Sidorczuk-Pietraszko [12] studied the spatial differences in household carbon intensities between different regions in Poland by means of exponential decomposition analysis (IDA); Rong [13] also found that there is an obvious spatial correlation between land-use carbon emissions in Chinese provinces, and thus suggested that China should strengthen the inter-provincial cooperation in order to achieve an overall emission reduction across the country.…”
Section: Land Use and Carbon Emissionsmentioning
confidence: 99%
“…Research on the differential responsibility for carbon emission reductions has mainly centered on the "polluter pays" principle, from which the principles of "responsibility within national territories" and "producer burden of pollution" have been derived [23]. Depending on the principles of "producer burden of pollution" and "consumer burden of pollution", scholars have put forward new principles such as "common sharing between importing and exporting countries" [12], "common sharing between producers and consumers" [13], and "common sharing between upstream and downstream of the industrial chain" according to different research objects [24,25].…”
Section: Carbon Emissions From Industriesmentioning
confidence: 99%